Literature Review: Modern Wound Care Management in Patients With Chronic Wounds - Zilfan Syahhani; Gipta Galih Widodoi (International Forum of Researchers and Lecturers, 2026)
Modern wound care using the moist wound healing principle is an effective approach to accelerate the healing process of chronic wounds, particularly diabetic foot ulcers. This study is a descriptive literature review aimed at analyzing the effectiveness of modern wound care based on previous research findings. Five articles were included, consisting of cross-sectional, true experimental, quasi-experimental, case study, and comparative study designs published between 2023 and 2025. Data were obtained from Google Scholar, PubMed, and GARUDA using keywords related to modern wound care and moist wound healing. The results show that modern wound care interventions such as honey hydrogel, moist wound healing, and home care–based modern dressing consistently improve wound healing outcomes, reduce wound scores, and enhance granulation tissue formation compared to conventional care. In addition, patient knowledge and family support also contribute to successful wound healing. In conclusion, modern wound care is effective in managing chronic wounds, especially in diabetic patients, and is recommended as an evidence-based nursing practice standard.